2018
DOI: 10.1111/jfpe.12857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermosonication on the quality attributes of star fruit juice

Abstract: The effect of pasteurization and thermosonication on the quality of star fruit (Averrhoa carambola) juice was reported in the present study. Freshly extracted star fruit juice was pasteurized and thermosonicated to compare the effect on physiochemical properties, antioxidant activity, total phenolic content (TPC), total flavonoid content (TFC), ascorbic acid levels, microbial populations, and sensorial properties. The results were compared with the raw star fruit juice. The treatments did not show any signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 43 publications
12
58
0
1
Order By: Relevance
“…From this physicochemical analysis of star fruit juice, the ascorbic acid content in fresh star fruit juice was found as 24.17 ± 0.70 mg/100 ml juice. Our result was more or less similar to the findings reported by Nayak et al [24], who were found the ascorbic acid content of 24.8 ± 0.71 mg/100 mL in the start fruit juice. Fig.…”
Section: Effect Of Thermal Treatment Condition On Ascorbic Acid Contesupporting
confidence: 93%
See 1 more Smart Citation
“…From this physicochemical analysis of star fruit juice, the ascorbic acid content in fresh star fruit juice was found as 24.17 ± 0.70 mg/100 ml juice. Our result was more or less similar to the findings reported by Nayak et al [24], who were found the ascorbic acid content of 24.8 ± 0.71 mg/100 mL in the start fruit juice. Fig.…”
Section: Effect Of Thermal Treatment Condition On Ascorbic Acid Contesupporting
confidence: 93%
“…Both the raw juice and heat samples showed the TSS value of 6.8 ºBrix. About the same effects were shown earlier by different researchers on their works on different fruit juices [24]. Only a little increase in TSS has happened and it was estimated as 7.0 ºBrix when the juice was heat 90°C for 30-40 min.…”
Section: Effect Of Thermal Treatment Condition On the Ph And Total Sosupporting
confidence: 78%
“…To determine the free radical scavenging activity DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl) is used as per method adopted by (Nayak, Chandrasekar, & Kesavan, ) by using a spectrophotometer Perkin Almer (Model: a‐25, USA).…”
Section: Methodsmentioning
confidence: 99%
“…TS treatments resulted in the same lethality values as required by the conventional PS or sterilization processes (Guerrouj, Sánchez-Rubio, Taboada-Rodríguez, Cava-Roda, & Marín-Iniesta, 2016). TS process is mainly focused on the inactivation of spoilage microorganisms and enzymes in khoonphal (Raju & Deka, 2018), star fruit (Nayak et al, 2018), apple (Abid et al, 2013), mulberry (Dinçer & Topuz, 2015), and pear juices (Saeeduddin et al, 2015).…”
Section: Practical Applicationsmentioning
confidence: 99%